GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 40095 species occurrences available in GBIF matching the query: TaxonKey: Xylocopa Latreille, 1802. The dataset includes 40095 records from 127 constituent datasets: 3198 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 11 records from International Barcode of Life project (iBOL). 8 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 402 records from Computarización de abejas de la colección entomológica de la Frontera Sur. 2975 records from Bee Biology and Systematics Laboratory. 2 records from UPRM Invertebrate Collection. 1 records from AntWeb. 69 records from Zoology (Museum of Evolution - Uppsala). 157 records from Lund Museum of Zoology - Insect collections (MZLU). 44 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 474 records from Hymenoptera specimen database of Kyushu University. 13 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 1 records from Artdata. 145 records from Museum Victoria provider for OZCAM. 440 records from Diversidad de abejas (Hymenoptera: Apoidea) de la Reserva de la Biosfera El Triunfo, Chiapas. 10 records from Abejas silvestres (Hymenoptera: Apoidea) de la región Praderas de Tokio-El Potosí - Sierra Mazmorras - Cañón de Iturbide, Coahuila y Nuevo León, México. 974 records from Insecta of Costa Rica (INBio). 7 records from Données ONF Faune-Flore-Fonge. 81 records from Museum of Comparative Zoology, Harvard University. 2 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 733 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 1259 records from iNaturalist Research-grade Observations. 23 records from Recent Invertebrates Specimens. 1499 records from AM: Terrestrial Insect Collections (1896-2000). 9 records from Estonian Museum of Natural History. 12 records from Estonian University of Life Sciences. 8 records from Essig Museum of Entomology. 1 records from Rund ums Ökohaus (Würzburg). 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 1 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 1032 records from Illinois Natural History Survey Insect Collection. 152 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1300 records from naturgucker. 30 records from Cleveland Museum of Natural History.. 59 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn).. 6 records from Centre for Biodiversity Genomics (BIOUG). 149 records from Museu Paraense Emilio Goeldi - Hymenoptera Collection. 8 records from ZUEC-HYM - Coleção de Hymenoptera do Museu de Zoologia da UNICAMP. 3 records from Packer Collection /Madagascar. 104 records from Insekten Sachsen. 1 records from BioBlitz Barcelona 2010-14. 371 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 71 records from Northern Territory Museum and Art Gallery provider for OZCAM. 36 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 4 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 3 records from Insect (NHMC-IN). 6 records from Insect (HUNM-IN). 37 records from Insect (JNHM-IN). 4 records from Insect (MNHM-IN). 832 records from IZIKO South Africa Museum Collection (1800-2013). 754 records from Coleção de Entomologia do Laboratório de Biologia Vegetal. 39 records from Natural History Museum (London) Collection Specimens. 2 records from Collection Hymenoptera SMF. 2442 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 2 records from Macaulay Library Audio and Video Collection. 30 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 5 records from Catálogo de insectos de la colección del Centro de Entomología. 578 records from Biodiversidad de la apifauna de Yucatán. 212 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 38 records from Ibaraki Nature Museum, Arthropoda collection. 32 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 297 records from NMNH Extant Specimen and Observation Records. 2 records from Bees of Canada / Joker's Hill collection. 3 records from Kashihara City Museum of Insect. 11 records from Insect Specimen Database of Fukui City Museum of Natural History. 9 records from Osaka Prefectural Minoh Park Insects Museum. 112 records from Hymenopteran specimen database of Osaka Museum of Natural History. 1 records from Individual Sightings. 275 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 16 records from Biologiezentrum Linz. 92 records from Insect specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 11 records from Itami City Museum of Insects. 394 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 38 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 453 records from Coleção Entomológica Moure e Costa. 342 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 73 records from Laboratório de Ecologia e Biogeografia de Insetos da Caatinga. 144 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 1 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 1 records from Schlern - (Bozen). 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 22 records from Colorado Plateau Museum of Arthropod Biodiversity. 1 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 54 records from Natural History Museum, University of Tartu. 65 records from Colección Nacional de Entomología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 1 records from Lustadter Wald .. 6 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 5 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 11 records from Gunma Museum of Natural History, Insect Specimen. 6 records from Insect Collection of Natural History Museum and Institute, Chiba. 1 records from Artenvielfalt am Schlern. 5 records from Biological and palaeontological collection and observation data MNHNL. 698 records from Entomology Division, Yale Peabody Museum. 285 records from CNIN/Abejas de México/Apoidea. 1446 records from Insect (KNAM-IN). 10 records from Museum of Southwestern Biology, Division of Arthropods. 7 records from Queensland Museum provider for OZCAM. 2881 records from ARC-PPRI: Collection of Southern African bees (1800-2007). 306 records from ArtenFinder. 7406 records from Snow Entomological Museum Collection. 42 records from Geographically tagged INSDC sequences. 5 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 19 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - World - Bees. 1 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 9 records from Colección Entomológica CDMB. 87 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 15 records from Colección de Entomología - Hymenoptera - Aculeata. 152 records from Instituto de Ciencias Naturales. 2 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 7 records from Données ONF Faune-Flore-FOnge. 5 records from Hymenoptera. 542 records from Natural History Museum Rotterdam (NL) - Insecta collection. 2719 records from Catalogue of Afrotropical Bees. 14 records from Australian Museum provider for OZCAM. 22 records from Entomology at ZMUC, Natural History Musem of Denmark. 10 records from Colección nacional de zoología. 2 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 4 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 9 records from Guadeloupe_Insectes. 7 records from Anymals+plants - Citizen Science Data. 2 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from UAM Insect Observations (Arctos). 18 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 3 records from Species observations during citizen science expeditions. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences